2005
DOI: 10.1128/aem.71.7.3599-3607.2005
|View full text |Cite
|
Sign up to set email alerts
|

Algal Viruses with Distinct Intraspecies Host Specificities Include Identical Intein Elements

Abstract: Heterosigma akashiwo virus (HaV) is a large double-stranded DNA virus infecting the single-cell bloomforming raphidophyte (golden brown alga) H. akashiwo. A molecular phylogenetic sequence analysis of HaV DNA polymerase showed that it forms a sister group with Phycodnaviridae algal viruses. All 10 examined HaV strains, which had distinct intraspecies host specificities, included an intein (protein intron) in their DNA polymerase genes. The 232-amino-acid inteins differed from each other by no more than a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 55 publications
(45 reference statements)
1
87
0
Order By: Relevance
“…The detection of inteins from all of our samples in this study, the presence of a variety of putative inteins from every station from the Global Ocean Survey data set (Yooseph et al, 2007) and the presence of DNA polymerase I motif C inteins in the phycodnavirus isolates HaV (Nagasaki et al, 2005) and CeV (Monier et al, 2008) all suggest that inteins are common among marine viruses. This raises the question of how DNA polymerase I motif C inteins are acquired by phycodnaviruses.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The detection of inteins from all of our samples in this study, the presence of a variety of putative inteins from every station from the Global Ocean Survey data set (Yooseph et al, 2007) and the presence of DNA polymerase I motif C inteins in the phycodnavirus isolates HaV (Nagasaki et al, 2005) and CeV (Monier et al, 2008) all suggest that inteins are common among marine viruses. This raises the question of how DNA polymerase I motif C inteins are acquired by phycodnaviruses.…”
Section: Discussionmentioning
confidence: 97%
“…However, we found that prasinovirus-like phylotypes (and KBvp-8 in particular) dominated both the winter 2006 sample, which was prefiltered, and the summer samples, which were not. Some PCR bias does seem likely, as it has been reported that the AVS primers do not amplify the DNA polymerase gene of several representative members of genera within the family (Sandaa et al, 2001;Nagasaki et al, 2005). Different approaches, such as quantitative PCR assays targeting specific viral groups, will be needed to determine the actual in situ abundance of prasino-like viruses relative to other genera within the family Phycodnaviridae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome size of HcV was estimated using pulsed-field gel electrophoresis (PFGE); and partial genome sequencing of HcRNAV and HcV were conducted according to the methods described by Nagasaki et al (2005a) and Nagasaki et al (2005b), respectively.…”
Section: Analysis Of the Virus Genomementioning
confidence: 99%
“…It has also been proposed on several occasions that sediments can constitute a potentially important reservoir of infectious bacteriophages [67], cyanophages [68] or algal viruses [69]. However, no processes involving the recruitment of viruses into or their release from sediments had so far been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 99%